2020
DOI: 10.18480/jjae.22.0_41
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Rural Policy Development in Japan: The Decay and Future Outlook of Rural Communities

Abstract: The aim of this study is to review criticalliy the rural policy development after the Basic Law on Food, Agriculture and Rural Areas established in 1999. The following points were found. An important feature of Japanese rural policy is the use of the rural community, which has a long history. The purpose of rural policy shifted from the promotion of rural society to the management of local resources. The key to future rural policy is to support the declining rural community and promote endogenous development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Ando ( 2020 ) suggests that future rural policies should support communities in declining collectivities and promote endogenous development. Shoyama et al ( 2021 ) showed that the factors of collective activities within and between communities are more significant than collaboration with outsiders in preventing abandoned farmland.…”
Section: Resultsmentioning
confidence: 99%
“…Ando ( 2020 ) suggests that future rural policies should support communities in declining collectivities and promote endogenous development. Shoyama et al ( 2021 ) showed that the factors of collective activities within and between communities are more significant than collaboration with outsiders in preventing abandoned farmland.…”
Section: Resultsmentioning
confidence: 99%
“…At the last year's symposium, the evaluation of the current situation was discussed for 20 years from the Basic Law on Food, Agriculture and Rural Areas established in 1999. Mr. Mitsuyoshi Ando made a report on rural policy, entitled "A Critical Review of the Rural Policy Development in Japan: The Decay and Future Outlook of Rural Communities" (Ando, 2020).…”
Section: Introductionmentioning
confidence: 99%